2017
DOI: 10.1111/nph.14610
|View full text |Cite
|
Sign up to set email alerts
|

Heat girdling does not affect xylem integrity: an in vivo magnetic resonance imaging study in the tomato peduncle

Abstract: Heat girdling is a method to estimate the relative contribution of phloem vs xylem water flow to fruit growth. The heat girdling process is assumed to destroy all living tissues, including the phloem, without affecting xylem conductivity. However, to date, the assumption that xylem is not affected by heat girdling remains unproven. In this study, we used in vivo magnetic resonance imaging (MRI) velocimetry to test if heat girdling can cause xylem vessels to embolize or affect xylem water flow characteristics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…However, we found that phloem girdled fruit continued growing at the same rate as ungirdled fruit under water stress indicating that in this species fruit water is predominantly supplied by the xylem. This result is supported by previous studies in tomato (Van De Wal et al, 2017;Windt et al, 2009). By demonstrating that the xylem is the main source of water supplying reproductive tissues even during periods of water stress, these data emphasize the special relevance of the cavitation resistance of xylem in the peduncle for understanding fruit growth and survival in water stress.…”
Section: Fruit Water Volume Is Supplied By Xylemsupporting
confidence: 87%
See 2 more Smart Citations
“…However, we found that phloem girdled fruit continued growing at the same rate as ungirdled fruit under water stress indicating that in this species fruit water is predominantly supplied by the xylem. This result is supported by previous studies in tomato (Van De Wal et al, 2017;Windt et al, 2009). By demonstrating that the xylem is the main source of water supplying reproductive tissues even during periods of water stress, these data emphasize the special relevance of the cavitation resistance of xylem in the peduncle for understanding fruit growth and survival in water stress.…”
Section: Fruit Water Volume Is Supplied By Xylemsupporting
confidence: 87%
“…We compared the growth rate of fruit with intact xylem and phloem to that of fruit with only intact xylem to determine the relative importance of xylem and phloem water delivery for fruit expansion during water stress. Phloem tissue was selectively killed by heat girdling the pedicel, according to Guichard, Gary, Leonardi, and Bertin (2005) and Van De Wal, Windt, Leroux, and Steppe (2017). In brief, a length of insulated nichrome wire (length, 0.5 m; diameter, 0.25 mm) was coiled around the pedicel between the peduncle joint and the abscission zone, covering half of the total 8mm length and an electrical current was applied via a transformer to raise the temperature to 75 o C for 1 min.…”
Section: Phloem Girdlingmentioning
confidence: 99%
See 1 more Smart Citation
“…The xylem depth was ascertained beforehand by sectioning and examining stem crosssections to determine the optimal amount of bark to remove. Although not tested in the present work, recent studies have shown that stem girdling does not affect the xylem integrity (Van de Wal et al, 2017). In that case, the authors tested heat girdling in a herbaceous species (tomato), whereas, in our study, we did not heat the un-barked stems and we measured a woody plant, and so stem xylem should not be affected by bark removal.…”
Section: Stem Preparationmentioning
confidence: 79%
“…Care was taken not to allow steam to damage the fruit itself. With steam-girdling, all cells in the steamed region of the pedicel are killed and phloem transport (a living process) is interrupted, whereas xylem transport (a non-living process) is unaffected [ 7 , 17 ]. Fruit from the third group (D) were detached by cutting the pedicel thereby interrupting X and P. The cut end of the pedicel was sealed using a fast-curing epoxy glue (UHU plus schnellfest; UHU, Bühl/Baden, Germany).…”
Section: Methodsmentioning
confidence: 99%